(untitled) (Latakia University Journal - Economic and Legal Sciences Series, 2024)
The current research handles the reality of Tishreen University’s application of the benchmarking method, the research aimed to determine the extent of the university’s application of benchmarking types (internal benchmarking, performance benchmarking, and strategic benchmarking). The comprehensive inventory method was applied for administrators working at the university in (senior and middle management), consisting of (72) individual. The research relied on the questionnaire as a data collection tool. Several key findings were highlighted: The University applies the benchmarking method, as the results showed that the level of application of the University for both types of external benchmarking (performance benchmarking and strategic benchmarking) was high, while the level of application of internal benchmarking was medium. It indicates that the university conducts the external benchmarking greater than the internal comparison. Among the most important recommendations was the need to better apply internal benchmarking by identifying the units with the best performance, and identifying strengths and weaknesses within the university, to achieve improvements that contribute to provide better quality in services. Additionally, the need to pay greater attention to apply strategic benchmarking by setting clear and measurable goals associated with the university’s vision and mission about areas that can be improved by using strategic benchmarking, and analyzing the strategies of better universities and learning from them.